2003
DOI: 10.2135/cropsci2003.0577
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrin Expression and Drought Tolerance in Seven Wheat Cultivars

Abstract: The winter wheat (Triticum aestivum L.) producing region of the U.S. Pacific Northwest (PNW) is subject to periods of water deficit during sowing and grain filling. Improving the genetic adaptation of wheat to drought stress represents one of the main objectives of regional breeding programs. One biochemical response to dehydrative stress is the accumulation of a family of proteins called dehydrins, which are believed to protect membranes and macromolecules against denaturation. Although previous studies demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(57 citation statements)
references
References 23 publications
6
51
0
Order By: Relevance
“…Lopez and co-workers during their research found a correlation between the accumulation of dehydrin in seven winter wheat cultivars during the exposure to water deficit. Three of the tested cultivars showed a significantly enhanced expression of 24 kDa dehydrin in comparison with other genotypes (Lopez et al 2003). In control plants of other analyzed genotypes, the expression of these proteins was not detected.…”
Section: Late Embryogenesis Abundant Proteinsmentioning
confidence: 78%
“…Lopez and co-workers during their research found a correlation between the accumulation of dehydrin in seven winter wheat cultivars during the exposure to water deficit. Three of the tested cultivars showed a significantly enhanced expression of 24 kDa dehydrin in comparison with other genotypes (Lopez et al 2003). In control plants of other analyzed genotypes, the expression of these proteins was not detected.…”
Section: Late Embryogenesis Abundant Proteinsmentioning
confidence: 78%
“…A wheat dehydrin has been shown to increase dehydration tolerance in transgenic rice (Cheng et al, 2002). In addition, drought-induced accumulation of dehydrin proteins has been associated with drought tolerance in many plant species, especially annual crops (Close et al, 1993;Lopez et al, 2001;Lopez et al, 2003). DHNs have been extensively studied in barley, where a dispersed family of 12 Dhn genes was characterized (Choi et al, 1999;Zhu et al, 2000).…”
Section: Dehydrins (Dhns)mentioning
confidence: 99%
“…The average production of this crop in Bangladesh is low compared to other wheat growing countries because wheat is mainly grown under nonirrigated conditions during the dry winter (November to April) in Bangladesh (Hossain and Silva, 2013). Although the vast storage of soil moisture resulted from monsoon rain supports the plant growth favorably at the early stages of growth, the plant suffers from water stress at the reproductive stage when the residual soil moisture depletes (Lopez et al, 2003).…”
Section: Introductionmentioning
confidence: 99%